PENGARUH DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA GURU PONDOK PESANTREN HIDAYATUL MA’ARIFIYAH PANGKALAN KERINCI KABUPATEN PELALAWAN - Fitriani, Arika (Ikatan Sarjana Ekonomi Indonesia Cabang Pekanbaru, 2024)
The research carried out aims to reveal how work discipline and motivation influence the performance of Hidayatul Ma'arifiyah Islamic Boarding School Teachers in Pangkalan Kerinci, Pelalawan Regency. A quantitative approach was used in this research. The population of this study consisted of 50 teachers. Determination of sampling using non-probability sampling using total/census sampling. Total/census sampling is a sampling technique where the entire population is used as a sample. This research uses multiple regression analysis with the SPSS program. The research results show that work discipline has a positive and significant effect on teacher performance; motivation has a positive and significant effect on teacher performance, and the two variables work discipline and motivation have a positive and significant effect on teacher performance.